Hepatic nonoxidative disposal of an oral glucose meal in patients with liver cirrhosis - Schneiter, Philippe; Gillet, Michel; Chioléro, René; Jéquier, Eric; Tappy, Luc (Metabolism, clinical and experimental, 1999)
Seven patients with liver cirrhosis and five healthy subjects were studied over 4 hours after ingestion of a glucose meal to determine whether alterations of hepatic nonoxidative glucose disposal participate in the pathogenesis of impaired glucose tolerance. Hepatic uridyl-diphosphoglucose (UDPG) turnover was calculated from the isotopic enrichment of urinary acetaminophen glucuronide during continuous infusion of 13C-galactose and used as an index of hepatic glycogen synthesis. Patients with cirrhosis had postprandial hyperglycemia and decreased glucose clearance, but hepatic UDPG turnover was not altered (1.84 ± 0.29 mg/kg fat-free mass · min v 1.76 ± 0.15 in controls, nonsignificant). It is concluded that hepatic postprandial glycogen synthesis is unaltered in patients with advanced cirrhosis, demonstrating important hepatic functional reserve.